Ethanolic extract of Polygonum minus protects differentiated human neuroblastoma cells (SH-SY5Y) against H2O2-induced oxidative stress - Sayuti, Nor Hafiza; Zulkefli, Nabilah; Tan, Jen Kit; Saad, Norazalina; Baharum, Syarul Nataqain; Hamezah, Hamizah Shahirah; Bunawan, Hamidun; Ahmed, Qamar Uddin; Parveen, Humaira; Mukhtar, Sayeed; Alsharif, Meshari A.; Sarian, Murni Nazira (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Neuronal models are an important tool in neuroscientific research. Hydrogen peroxide (H2O2), a major risk factor of neuronal oxidative stress, initiates a cascade of neuronal cell death. Polygonum minus Huds, known as ‘kesum’, is widely used in traditional medicine. P. minus has been reported to exhibit a few medicinal and pharmacological properties. The current study aimed to investigate the neuroprotective effects of P. minus ethanolic extract (PMEE) on H2O2-induced neurotoxicity in SH-SY5Y cells. LC–MS/MS revealed the presence of 28 metabolites in PMEE. Our study showed that the PMEE provided neuroprotection against H2O2-induced oxidative stress by activating the Nrf2/ARE, NF-κB/IκB and MAPK signaling pathways in PMEE pre-treated differentiated SH-SY5Y cells. Meanwhile, the acetylcholine (ACH) level was increased in the oxidative stress-induced treatment group after 4 h of exposure with H2O2. Molecular docking results with acetylcholinesterase (AChE) depicted that quercitrin showed the highest docking score at −9.5 kcal/mol followed by aloe-emodin, afzelin, and citreorosein at −9.4, −9.3 and −9.0 kcal/mol, respectively, compared to the other PMEE’s identified compounds, which show lower docking scores. The results indicate that PMEE has neuroprotective effects on SH-SY5Y neuroblastoma cells in vitro. In conclusion, PMEE may aid in reducing oxidative stress as a preventative therapy for neurodegenerative diseases.